EVALUATION OF ESSENTIAL OILS AND CULTURAL PRACTICES FOR THE MANAGEMENT OF VARROA DESTRUCTOR - SANDEEP KOTWAL; DHARAM P. ABROL (The Bioscan, 2012)
Combination of different essential oils and cultural practices were evaluated for the management of Varroa destructor mites infesting Apis mellifera colonies during different seasons of the year. Different combinations were evaluated for management of Varroa mites infesting Apis mellifera colonies. The efficacy of different combination of treatments during different seasons was in the order: February-April: Queen caging + Cinnamon oil > Queen caging + Eucalyptus oil > Queen Caging + Menthol oil > Sulphur dust. However, during, May- July, Sulphur + oxalic acid was most effective followed by Sulphur + Formic acid > Sulphur + Lactic acid and >Sulphur dust, respectively. During August-October the Formic acid + Cinnamon oil was most effective followed by>Formic acid + Eucalyptus oil > Formic acid + Menthol oil and > Sulphur dust. In November- January the efficacy of different treatments was in the order Thymol + Oxalic acid > Thymol + Formic acid > Thymol + Lactic acid >Sulphur dust. The results clearly reveal that efficacy of different treatments vary with the seasons.